Leadership Standpoints A Practical Framework for the Next Generation of Nonprofit Leaders - Waisanen, Don (Social Sciences, 2021)
Offers a new leadership framework for the next generation of nonprofit professionals. Based on five years of data collected from the New York Community Trust Leadership Fellowship - designed to address leadership development gaps in the nonprofit sector. This title is also available as Open Access on Cambridge Core.